Screening of whole yeast free-cells and optimization of pH and temperature for fructooligosaccharides production - Flávia Deffert; Bruna Carla Agustini; Geraldo Picheth; Tania Maria Bordin Bonfim (Acta Scientiarum. Biological Sciences, 2017)
Fructooligosaccharides are catalyzed by β–fructofuranosidase enzyme, produced by many microorganisms. However, in order to achieve a more profitable, low time-consuming process with lower cost, researchers have sought alternatives. This study aimed to select and identify yeasts able to produce fructooligosaccharides and evaluate the influence of pH and temperature on their synthesis. Yeast suspensions, solutions of 500 g L-1 sucrose and three values of pH (4.5, 5.5, and 6.5) and temperature (40, 50, and 60ºC) were tested. Yeast species were identified by molecular techniques. Among 141 yeast isolates from grapes, 65 were able to synthesize fructooligosaccharides. The maximum concentration of fructooligosaccharides was 4.8% (w v-1), and Saccharomyces cerevisiae 222 produced 1-kestose and nystose.